Odpowiedzi

2009-12-06T20:20:36+01:00
A) x² + 6x + 9 = 0
(x+3)² = 0
x = -3

b) x² + 6x = 7
x² + 6x - 7 = 0
Δ = b² - 4ac = 36 + 28 = 64 = 8²
x₁ = -7
x₂ = 1

c) 3x²+2x-2=0
Δ = 4 + 24 = 28 = (2√7)²
x₁ = (-1 - √7)/3
x₂ = (-1 +√7)/3

d) 2x=5x²+1
5x² -2x +1 = 0
Δ = 4 - 20 = -16
Δ < 0

e) 2-4x=3x²
3x² +4x - 2 = 0
Δ = 16 + 24 = 40 = (2√10)²
x₁ = (-2 - √10)/3
x₂ = (-2 + √10)/3
2009-12-06T20:31:12+01:00
D) 3x²+2x-2=0
a=3,b=2,c=-2
Δ=4-4*3(-2)
Δ=4+24=28
√Δ=28=2√7
x₁=-2-2√7=2(-1√7)=-1√3
--------- ------- -------
6 6 3
x₂=2+2√2 =2(-1+√7) =-1+√7
------ ----------- -----
6 6 3